IκBζ facilitates protective immunity against Salmonella infection via Th1 differentiation and IgG production - Ahn, Jae Hee; Cho, Jaewon; Kwon, Bo Eun; Lee, Geun Shik; Yoon, Sung il; Kang, Seung Goo; Kim, Pyeung Hyeun; Kweon, Mi Na; Yang, Hyungjun; Vallance, Bruce A.; Kim, Young In; Chang, Sun Young; et al. (Scientific Reports, 2019)
Inhibitor of kappa B (IκB)-ζ transcription is rapidly induced by stimulation with TLR ligands and IL-1. Despite high IκBζ expression in inflammation sites, the association of IκBζ with host defence via systemic immune responses against bacterial infection remains unclear. Oral immunisation with a recombinant attenuated Salmonella vaccine (RASV) strain did not protect IκBζ-deficient mice against a lethal Salmonella challenge. IκBζ-deficient mice failed to produce Salmonella LPS-specific IgG, especially IgG2a, although inflammatory cytokine production and immune cell infiltration into the liver increased after oral RASV administration. Moreover, IκBζ-deficient mice exhibited enhanced splenic germinal centre reactions followed by increased total IgG production, despite IκBζ-deficient B cells having an intrinsic antibody class switching defect. IκBζ-deficient CD4+ T cells poorly differentiated into Th1 cells. IFN-γ production by CD4+ T cells from IκBζ-deficient mice immunised with RASV significantly decreased after restimulation with heat-killed RASV in vitro, suggesting that IκBζ-deficient mice failed to mount protective immune responses against Salmonella infection because of insufficient Th1 and IgG production. Therefore, IκBζ is crucial in protecting against Salmonella infection by inducing Th1 differentiation followed by IgG production.
Keywords: Adaptor Proteins, Signal Transducing; Administration, Oral; Animals; Cell Differentiation; Chronic Disease; Germinal Center; Immunity; Immunization; Immunoglobulin G; Inflammation; Interferon-gamma; Lipopolysaccharides; Mice, Inbred C57BL; Salmonella Infections; Salmonella typhimurium; Salmonella Vaccines; Th1 Cells; Vaccines, Attenuated; Virulence